Magnetic carbon materials as sorbents for water purification from petroleum products - Kazarinov, I. A.; Gumarova, Zh. M.; Askarova, A. Zh.; Гумарова, Ж. М.; Аскарова, А. Ж. (Ғылым және білім=Наука и образование=Science and education. - 2024. - № 3-2 (76). Ч. ІІ. - Р. 266-275, 2024)
The development of effective sorbents for water purification is crucial to reduce environmental pollution with petroleum products. A method for obtaining a complex adsorbent with magnetic properties for the elimination of oil spills from the water surface using a controlled magnetic field is proposed. In this study, methods for the synthesis of magnetite-carbon composites by co-deposition and the synthesis of magnetite-carbon composites by mechanical grinding in a ball mill were proposed. Magnetic carbon sorbents were synthesized using activated carbon and magnetic nanoparticles by co-deposition, after which physicochemical characteristics were obtained using methods such as infrared spectroscopy and X-ray fluorescence analysis. The adsorption capacity is estimated under conditions of competitive adsorption of water and oil on the surface of magnetite, coal and their composite. The results show that magneto-carbon materials have good adsorption efficiency, rapid separation from water due to their magnetic properties and excellent reusability, which makes them promising candidates for water purification. These results suggest that magneto-carbon sorbents can play a significant role in environmental remediation efforts by providing an effective solution for the treatment of water contaminated with petroleum products.